Child slavery in modern times - Newman, Shirlee Petkin (2000)
Discusses cases where children are forced to work against their wills in difficult and dangerous conditions in various countries around the world.
Includes bibliographical references (p. 55-56) and index.
Keywords: Child slaves -- Juvenile literature; Slavery -- Juvenile literature; Juvenile works